Seeds as a source of carbon, nitrogen, and phosphorus for seedling establishment in temperate regions: A synthesis - Lamont, Byron; Groom, Philip (Scientific Research Publishing Inc., 2013)
Seeds are a source of organic (carbon, C) and mineral (nitrogen, N and phosphorus, P) nutrients for the growing seedling. There is much information on seed mass and N and P contents, and the relationship between these and seedling mass. Within the world’s temperate regions, these collectively show that N and P concentrations remain constant or rise with increase in seed mass and that seeds are larger and more nutrient-enriched in poorer soils. Seed N and P were more important than seed C in accounting for seedling mass in 85% of studies we assessed. In nutrient- and water-limited environments that are not light-limited, large seeds routinely provision the seedling with N and P that enhance C-fixation and thus general growth in the first wet season. This system is so efficient that growth response to soil nutrients may be negligible in first-year seedlings arising from seeds > 15 mg mass, N content > 5 mg and P content > 1.6 mg. The elongating taproot system absorbs nutrients and maintains water uptake as soil water retreats, enhancing the chances of survival in the first dry season. We outline an interpretative scenario for the special role of large seeds (>15 mg) in nutrient- and water-limited environments that recognizes the critical role of N and P for photosynthesis in ensuring sufficient C-supply to the rapidly descending roots for effective drought-avoidance by the young plant.